2004
DOI: 10.2134/jeq2004.0837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cry3Bb Transgenic Corn and Tefluthrin on the Soil Microbial Community: Biomass, Activity, and Diversity

Abstract: Transgenic Bt corn expressing the Cry3Bb insecticidal protein active against corn rootworm (CRW) (Diabrotica spp.; Coleoptera: Chrysomelidae) was released for commercial use in 2003 and is expected to be widely adopted. Yet, the direct and indirect risks to soil microorganisms of growing this CRW-resistant Bt corn versus applying insecticides to control the rootworm have not been assessed under field conditions. The effects of CRW Bt corn and the insecticide tefluthrin [2,3,5,6-tetrafluoro-4-methylbenzyl (Z)-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 39 publications
10
59
0
2
Order By: Relevance
“…This is consistent with the results of several other studies that have reported no changes in the abundance or composition of bacterial and fungal communities in field soils where Bt corn was planted or in soils amended with Bt corn biomass and incubated under glasshouse conditions (Saxena and Stotzky, 2001a;Blackwood and Buyer, 2004;Devare et al, 2004Devare et al, , 2007Icoz et al, 2008). Similarly, the numbers of culturable bacteria and fungi, and the activity of enzymes involved in degrading Bt plant biomass did not differ significantly from those associated with non-Bt plant biomass, confirming laboratory observations that the Cry1Ab protein is not toxic to a spectrum of pure and mixed cultures of microbes (Koskella and Stotzky, 1997).…”
Section: Bacterial and Fungal Communities Colonizing The Surface Of Csupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the results of several other studies that have reported no changes in the abundance or composition of bacterial and fungal communities in field soils where Bt corn was planted or in soils amended with Bt corn biomass and incubated under glasshouse conditions (Saxena and Stotzky, 2001a;Blackwood and Buyer, 2004;Devare et al, 2004Devare et al, , 2007Icoz et al, 2008). Similarly, the numbers of culturable bacteria and fungi, and the activity of enzymes involved in degrading Bt plant biomass did not differ significantly from those associated with non-Bt plant biomass, confirming laboratory observations that the Cry1Ab protein is not toxic to a spectrum of pure and mixed cultures of microbes (Koskella and Stotzky, 1997).…”
Section: Bacterial and Fungal Communities Colonizing The Surface Of Csupporting
confidence: 92%
“…The Bt protein may also be released by decomposing plant residues incorporated into soil after crop harvesting. Thus far, no adverse effects have been reported on the abundance or diversity of bacterial or fungal communities in the rhizosphere of Bt corn (Blackwood and Buyer, 2004;Devare et al, 2004Devare et al, , 2007 or in soils into which ground residues have been added (Saxena and Stotzky, 2001a). Decreased rates of respiration from soils in which residues from six Bt crops had been incorporated were observed in one laboratory incubation (Flores et al, 2005), although no mechanism to explain these observations was proposed.…”
Section: Introductionmentioning
confidence: 97%
“…However, another comparison of samples from Bt and non-Bt maize fields revealed a lower abundance of nematodes in Bt fields (Griffiths et al, 2005). The compositions of bacterial communities (Devare et al, 2004;Baumgarte and Tebbe, 2005) and the relative abundances of bacterial classes (Brusetti et al, 2004) did not differ among Bt and non-Bt treatments. It should be noted that Brusetti et al (2004) found no difference in the abundance of spore forming bacteria, which includes Bacillus entomopathogens.…”
Section: Entomopathogensmentioning
confidence: 84%
“…Such recombinant products may thus potentially enter the rhizosphere as an additional nutrient source for the soil microbial community. However, studies so far indicated that alterations of the bacterial community structure of Bt-maize producing single Cry proteins were in the range of differences between conventional varieties or not detectable (Devare et al, 2004;Baumgarte and Tebbe, 2005;Miethling-Graff et al, 2010). Considering that these studies were based on classical cloning and sequencing approaches and/or on genetic fingerprinting, the lack of detection may in fact be linked to the relatively low sensitivity of such methods.…”
Section: Introductionmentioning
confidence: 99%